Geo-Congress 2019. selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, March 24-27, 2019, Philadelphia, Pennsylvania - Meehan, Christopher L.; Kumar, Sanjeev, 1964-; Pando, Miguel Angel, 1968-; Coe, Joseph T. (American Society of Civil Engineers, 2019)
Selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, held in Philadelphia, Pennsylvania, March 24-27, 2019. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 49 peer-reviewed papers on earthquake engineering and soil dynamics. Topics include: soil-structure interactions; liquefaction; seismic performance; numerical modeling; laboratory testing techniques; seismic hazard analysis; and site response. GSP 308 will be of interest to all practitioners and researchers working in the area of earthquake engineering.
Keywords: Geotechnical engineering -- Congresses.; Geotechnical engineering -- Case studies.; Soil dynamics -- Congresses.; Earthquake engineering -- Congresses.; Soil dynamics -- Case studies.; Earthquake engineering -- Case studies.; elektronické knihy; electronic books